The Market Structure-Performance Relationship in the International Insurance Sector - Pope, Nat; Ma, Yu-Luen (The Journal of risk and insurance, 2008)
This article tests the applicability of the structure-conduct-performance (SCP) hypothesis in the international nonlife insurance marketplace. We employ a panel data regression methodology that includes 23 nations (developed and developing countries) over the time period of 1996 to 2003. The results reveal that the interaction of market liberalization and market concentration shares a complex relationship with market profitability. Our results show that the expectations associated with the SCP hypothesis are supported when the levels of liberalization are low. However, for markets that are highly liberalized the presence of foreign insurers significantly alters the dynamics of nonlife insurance markets.